(untitled) (Journal of Information Technologies in Education (ITE), 2011)
The conceptual approaches to create the information-analytical system of educational management, which used modern methods of decision-making and simulation, web-technology are considered. The main criteria for selection of system development are: openness, free of charge, easy of use and independence of system software and hardware. The technology and the system itself meets the requirements as: focus on national and international standards in higher education, compliance with service-oriented architecture, ensure stable operation for a large number of users, support a clear division of users rights to obtain and change information resources, modularity of final product and its ability to integrate into the university corporate information system.